Serum proteomics analysis of lung transplant patients receiving different induction therapies - Nasrollahi-Shirazi, Shahrooz; Unterwurzacher, Markus; Berezhinskiy, Hatice Oya; Alemanno, Sophia; Hoetzenecker, Konrad; Aigner, Clemens; Jaksch, Peter; Mohr, Thomas; Kratochwill, Klaus; Benazzo, Alberto (Frontiers in Immunology, 2025)
IntroductionInduction therapy is widely used in lung transplantation to control the host alloresponse, reducing acute cellular rejection and improving graft survival. Despite its use, data on the biological effects of different induction agents remain limited.MethodsThis study examines serum proteomics profiles in lung transplant patients receiving alemtuzumab, anti-thymocyte globulin (ATG), or no induction therapy. Adult lung transplant recipients who underwent transplantation between 2007 and 2013 at the Medical University of Vienna were included. Using mass spectrometry (MS), serum samples were examined before transplantation (T1) and 12 months post-transplant (T2).ResultsAmong 102 patients (50 alemtuzumab, 34 ATG, 18 no induction), we identified significantly differentially expressed proteins over time and between groups at T2. In the alemtuzumab group, 40 proteins were differentially expressed (3 upregulated, 37 downregulated), in ATG, 22 proteins (3 upregulated, 19 downregulated), and none in the no-induction group. At T2, two proteins (fibulin-1 and fetuin-B) were downregulated between alemtuzumab and no induction, with no significant differences between alemtuzumab and ATG or ATG and no induction.DiscussionOur findings suggest alemtuzumab may have a stronger effect on circulating proteome. Further studies are warranted to elucidate the underlying mechanisms and explore potential clinical implications.